ABNORMALITAS SELULER DAN MOLEKULER PADA RETT SYNDROME YANG DIPENGARUHI MUTASI GEN MeCP2: CELLULAR AND MOLECULAR ABNORMALITIES IN RETT SYNDROME INFLUENCED BY MUTATION IN THE MeCP2 GENE - Lestari, Ira Cinta; Suryani Eka Mustika (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Rett Syndrome (RTT) is a postnatal neurological developmental disorder linked to the X chromosome, caused by mutations in the gene encoding methyl-CpG binding protein 2 (MeCP2). MeCP2 acts as a transcription regulator, functioning both as a repressor and an activator of its target genes, playing a crucial role in maintaining cellular homeostasis in the nervous system. Dysfunction in MeCP2 leads to various neuropsychiatric abnormalities, including developmental, motor, and cognitive impairments characteristic of RTT. Studies suggest that MeCP2 defects are not permanent, presenting opportunities to restore normal function through targeted therapeutic strategies. Molecular-level interventions aim to correct gene expression and related protein functions, thereby improving nervous system function and the quality of life for patients. This article reviews the molecular mechanisms underlying RTT, including abnormalities in neuronal structure and function, as well as recent therapeutic advancements such as gene therapy, epigenetic modulation, and pharmacological approaches to mitigate the effects of MeCP2 dysfunction. These studies offer new hope for the development of personalized therapies for RTT patients. AbstrakRett Syndrome (RTT) adalah gangguan perkembangan neurologis pasca kelahiran yang terkait dengan kromosom X, disebabkan oleh mutasi pada gen yang mengkode methyl-CpG binding protein 2 (MeCP2). MeCP2 berfungsi sebagai regulator transkripsi, baik sebagai penghambat maupun aktivator gen targetnya, sehingga memiliki peran penting dalam menjaga homeostasis fungsi seluler di sistem saraf. Disfungsi MeCP2 mengarah pada berbagai abnormalitas neuropsikiatrik, termasuk gangguan perkembangan, motorik, dan kognitif yang menjadi ciri khas RTT. Berbagai studi menunjukkan bahwa defek pada MeCP2 tidak bersifat permanen, memberikan peluang untuk mengembalikan fungsi normal melalui strategi terapi yang ditargetkan. Intervensi pada tingkat molekuler bertujuan memperbaiki ekspresi gen dan fungsi protein terkait, sehingga meningkatkan fungsi sistem saraf dan kualitas hidup pasien. Artikel ini meninjau mekanisme molekuler yang mendasari RTT, termasuk abnormalitas pada struktur dan fungsi neuron, serta upaya terapi terbaru, seperti penggunaan terapi gen, modulasi epigenetik, dan pendekatan farmakologis untuk memitigasi dampak gangguan MeCP2. Studi-studi ini membuka harapan baru dalam pengembangan terapi personal untuk penderita RTT.